The Influence of The Principal’s Supervision and Teacher’s Pedagogical Competence on Teacher’s Performance - Maulia, Nursanti; Widayatsih, Tri; Nurlina, Nurlina (Journal of Social Work and Science Education, 2023)
This study aims to examine 1) the effect of principal supervision on teacher performance 2) the effect of pedagogic competence on teacher performance, and 3) the effect of principal supervision and teacher pedagogic competence together on teacher performance in schools. The method used in this research is quantitative. The data collection tool uses observation, questionnaire and documentation methods. Data analysis using data regression. The results of the study stated that 1) there was a significant influence between the principal’s supervision value on teacher performance, 2) there was a significant influence between the value of teacher pedagogic competence on teacher performance, meaning that teacher performance is influenced by teacher pedagogic competence, and 3) there was a significant influence between principal supervision and pedagogical competence on teacher performance scores, statistically the data used proves that all independent variables. The conclusion from this study is that in improving teacher performance it is necessary to have school principal supervision and pedagogical competence.